A253 RETINOIC ACID RECEPTOR ALPHA IS A NEGATIVE REGULATOR OF INTESTINAL EPITHELIAL TSLP GENE EXPRESSION. (15th March 2019) - mahmood, R; Chan, R; Beck, P; Jijon, H
Abstract: Background: We have recently described decreased myeloid cell numbers in the large and small intestines of intestinal-specific Retinoic Acid Receptor (RAR) alpha-deficient mice (Villin-Cre RAR -/- mice). We therefore hypothesized that Retinoic Acid (RA) and its receptors may regulate the expression of intestinal Thymic Stromal Lymphopoietin (TSLP), an important cytokine involved in Th2-type immunity known to play critical roles in the maintenance of peripheral CD4 + T cell homeostasis via the modulation of activation/maturation of myeloid cells and decreased IL-12 production. Importantly, TSLP levels are decreased in Crohn's disease (CD) where inflammation is driven by IL-12. Furthermore, there is epidemiologic data suggesting that the RAR agonist all-trans retinoic acid (ATRA, Accutane © ) may be protective in CD. Aims: To determine whether retinoic Acid is a positive regulator of TSLP expression via activation of RAR alpha in Intestinal Epithelial Cells (IECs). Methods: We examined TSLP expression in the colons of Villin-Cre RAR -/- mice. Epithelial cells were isolated from the crypts and surface colonic epithelium and RNA isolated and analyzed via qRT-PCR. TSLP expression in the surface colonic epithelium was compared to that of wild-type littermates. In order to determine whether changes in TSLP expression were due to cell intrinsic effects, we sought to generate a RARalpha IEC knockout cell line. Using CRISPR/CAS9 we targeted exon 5 in the open reading frame of the RARalpha gene in Mode-K murine IECs. Targeted cells were selected in puromycin, cloned and CRISPR cleavage confirmed using Surveyor assays. Knockdown of RARalpha was assessed using RARluciferase assays. Results: TSLP expression in surface colonic epithelium was elevated 2.3 fold in RARalpha villin-cre mice compared to wild type litter mates. In contrast, crypt TSLP expression was unchanged, as expected given absence of Cre expression in this compartment. We successfully generated partial RARalpha deficient Mode-K cells based on the results of Surveyor assays and RAR-luciferase activity assays. TSLP expression was elevated 2.3 fold in the Mode-K RARalpha CRISPR clones versus parent Mode-K cells. Conclusions: TSLP expression is controlled at least in part by RAR alpha in colonic IECs where it may act as a repressor of TSLP promoter transactivation. This suggests that retinoic acid, a dietary factor, may influence myeloid and T cell function via effects on epithelial TSLP expression and suggests a mechanism whereby Accutane © (ATRA) may affect CD. Funding Agencies: CCCCumming School of Medicine